The vulnerability and resilience of a city's water footprint: The case of Flagstaff, Arizona, USA. Issue 4 (8th April 2016) - Rushforth, Richard R.; Ruddell, Benjamin L.
Abstract: Research has yet to operationalize water footprint information for urban water policy and planning to reduce vulnerability and increase resilience to water scarcity. Using a county‐level database of the U.S. hydro‐economy, NWED, we spatially mapped and analyzed the Water Footprint of Flagstaff, Arizona, a small city. Virtual water inflow and outflow networks were developed using the flow of commodities into and out of the city. The power law distribution of virtual water trade volume between Flagstaff and its county trading partners broke at a spatial distance of roughly 2000 km. Most large trading partners are within this geographical distance, and this distance is an objective definition for Flagstaff's zone of indirect hydro‐economic influence—that is, its water resource hinterland. Metrics were developed to measure Flagstaff's reliance on virtual water resources, versus direct use of local physical water resources. Flagstaff's reliance on external water supplies via virtual water trade increases both its hydro‐economic resilience and vulnerability to water scarcity. These methods empower city managers to operationalize the city's Water Footprint information to reduce vulnerability, increase resilience, and optimally balance the allocation of local physical water supplies with the outsourcing of some water uses via the virtual water supply chain. Key Points: A spatially detailed water footprint maps a city's hydro‐economic network Trade indirectly increases both Flagstaff's vulnerability and resilience to water scarcity The network method establishes Flagstaff's hydro‐economic "hinterland" as a 2000 km radius